Traffic Safety Socialization for Prospective Motor Vehicle Drivers, at Sanggar Bimbingan At-Tanzil, Kuala Lumpur, Malaysia - Mukarom, Su’udi Al; Fistcar, Wawarisa Alnu; Zubet, Muhammad Asin; Hairudin, Aldi Mashar; Agustina, Juwita (Fakultas Teknik Universitas Diponegoro, 2024)
Malaysia is the main destination country for placing Indonesian Migrant Workers (TKI) to get a better life. According to the Indonesian Migrant Workers Protection Agency (BP2MI), Malaysia is the third-highest country for the placement of Indonesian migrant workers, namely 34,403 people in the period January–July 2024. During the years of working in Malaysia, many Indonesian Migrant Workers (PMI) have built families in Malaysia and even had children who grew up in Malaysia. Many children born and raised from marriages between Indonesian immigrant workers do not have sufficient documents to attend state or private schools. Many of these children are 15 years old, or the age at which they will soon have the right to have a driving license. Young drivers continue to be overrepresented in the failure of the transportation system as evidenced by the loss of life and injury resulting from road accidents. Transportation system failure is the leading cause of death among young people worldwide. Moreover, most of the congested roads, loss of life, and injury among young drivers aged 15-29 years occur in low- and middle-income countries. Traffic safety issues among children and adolescents occur at a global level, including in Southeast Asian countries. In Southeast Asian countries, many teenagers in junior high school tend to be more independent and travel alone more than elementary school children, so they need understanding and skills to behave safely when carrying out traffic activities on the road. One method to increase awareness and culture of road safety is through education and promotion of the importance of traffic safety. This study is intended to obtain an overview of the level of traffic safety and awareness of traffic behavior in the community, especially among junior high school students so that the level of safety and the need for safety education can be identified and analyzed to determine the form of program that can be implemented both between schools and students and the government with students.